Resurgence of blackwater fever among children in sub-Saharan Africa: a scoping review protocol - Julian Abeso; Francis Okello; Peter Olupot-Olupot; George Paasi; Carolyne Ndila; Florence Alaroker; Glorias Asiimwe (BMJ Open)
Introduction Blackwater fever (BWF), a complication of malaria, has in the past been considered as a rare complication of malaria in children living in high transmission settings. More recently, however, a growing number of paediatric clusters of BWF cases have been reported predominantly in sub-Saharan Africa (SSA). The aim of this study is to map evidence on BWF among children in SSA from 1 January 1960 to 31 December 2021.Methods and analysis This review will be guided by Arksey and O’ Malley’s methodological framework for scoping reviews with methodological refinements by Levac et al and will comply with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews’ guidelines. Five electronic databases (MEDLINE via PubMed, Embase, the Cochrane Library, the Cumulative Index to Nursing and Allied Health Literature (CINAHL) and PsycINFO) will be systematically searched using predefined keywords. In addition, reference lists of included articles will be searched. Our multidisciplinary team has formulated search strategies and two reviewers will independently complete study eligibility screening, final selection and data extraction. A third reviewer will adjudicate the final decision on disputed articles. Bibliographic data and abstract content will be collected and analysed using a data-charting tool developed iteratively by the research team.Ethics and dissemination This scoping review being a secondary analysis does not require ethics approval. We anticipate results of this review will broaden understanding of paediatric BWF in SSA and identify its research gaps in SSA. We will be disseminating results through journals and conferences targeting primary care providers.